Application of Three-Dimensional Pseudocontinuous Arterial Spin Labeling Perfusion Imaging in the Brains of Children With Autism - Tang, Shilong; Liu, Xianfan; Ran, Qiying; Nie, Lisha; Wu, Lan; Pan, Zhengxia; He, Ling (Frontiers in Neurology, 2022)
Objective: To explore the application of three-dimensional pseudocontinuous arterial spin labeling (3D-PCASL) perfusion imaging in the brains of children with autism to understand the characteristics of cerebral blood perfusion in autistic children. Methods: A total of 320 autistic children (160 males and 160 females) aged between 2 and 18 years and 320 age- and sex-matched healthy children participated in the study. All children were scanned by 3.0T magnetic resonance axial T1 FLAIR, T2 FLAIR, 3D-T1 and 3D-PCASL sequences. After postprocessing, CBF values in each brain region of autistic children and healthy children at the same age were compared and analyzed. Furthermore, CBF characteristics in each brain region of autistic children at various ages were determined. Results: The CBF values of the frontal lobe, hippocampus, temporal lobe and caudate nucleus of autistic children are lower than those of healthy children (P<0.05). Additionally, with increases in of the ages of autistic children, the number of brain regions with decreased CBF values gradually increases. ROC analysis results show that the CBF values of the frontal lobe, hippocampus, temporal lobe and caudate nucleus can distinguish children with autism (AUC>0.05, P<0.05). Conclusion: 3D-PCASL shows lower brain CBF values in children with autism.